Fabrication and characterization of PZT/CuO thin film - Tharathip Sreesattabud (2018)
Pb(Zr0.52Ti0.48)O3or PZT thin films embedded with CuO nano-particles were successfully prepared by a hybrid sol-gel process. In this process, CuO (0, 0.1, 0.2, 0.3, 0.4, 0.5 and 1wt%) nanopowder was suspended in an organometallic solution of PZT, and then coated on platinised silicon substrates using a spin-coating technique. X-ray diffraction patterns showed a perovskite phase in all the films. The CuO particles were not detected in the film, but the small amount of second phase was present when CuO concentration was above 0.4 wt%. The addition of CuO nano-particles also affected the orientation of PZT films. The CuO nano-particles were generally found to reduce both dielectric and ferroelectric properties of PZT films. However, at 0.2 wt% CuO concentration, the film exhibited good ferroelectric properties which were comparable to those of pure PZT thin films. © 2013 Copyright Taylor and Francis Group, LLC.